Anorexia nervosa and a psychosomatic investigation. - Bouça, D; Sampaio, D; Cordeiro, J C (Acta Médica Portuguesa, 1992)
The paper begins with a revision of diagnostic criteria of Anorexia Nervosa (AN), stressing the importance of early diagnosis and transitional forms between AN and Bulimia Nervosa. A retrospective study of 13 female patients with AN, treated during 1990 in Lisbon Psychiatric University Clínica (Hospital de Santa Maria, Lisboa) is then described. The Authors outline some common characteristics of the sample, many difficulties in the early relationship mother-child, shown by maternal unsatisfaction on feeding the baby and with changing of food. Concluding, the Authors point out some directions for eating disorder's investigation, starting with a multidisciplinary work including biological and cultural factors and understanding of individual development and family dynamics.